A new species of the genus Catillopecten (Bivalvia: Pectinoidea: Propeamussiidae): morphology, mitochondrial genome, and phylogenetic relationship - Lin, Yi-Tao; Li, Yi-Xuan; Sun, Yanan; Tao, Jun; Qiu, Jian-Wen (Frontiers in Marine Science, 2023)
Catillopecten is a small genus of deep-sea glass scallops, but its diversity is poorly known in many parts of the world ocean. We described C. margaritatus n. sp. (Pectinoidea: Propeamussiidae), and performed morphological analyses and DNA sequencing, and estimated the divergence time of scallops based on samples collected from Haima cold seep in the South China Sea. Morphologically, the new species can be distinguished from congeneric species by its large shell size, relatively small auricle length, absence of monocrystal aerials, presence of longitudinal radial ridges on the left valve, and the alternated rounded striae and distal and proximal growth lines of prisms on the right valve. Anatomically, this new species can be distinguished from C. vulcani by its anteriorly located auriculate gills, compared to the centrally located lamellar gills of the latter, and the different locations of the pericardium. Sequence comparison and phylogenetic analysis based on the 18S rRNA fragments supported the placement of the new species in Catillopecten. We also report the mitogenome of C. margaritatus n. sp. as the only reported mitogenome of the family Propeamussiidae, which differs from those of other scallops substantially in gene order arrangement. Divergence time estimation revealed that Propeamussiidae and Pectinidae diverged in the early Carboniferous, while Catillopecten and Parvamussium diverged during the late Cretaceous to early Eocene. Finally, we presented a key to the species of Catillopecten.